APPLICATION OF THE MIND MAPPING MODEL IN IMPROVING THE ABILITY OF WRITING EXPOSITION TEXTS IN CLASS X MIPA 4 STUDENTS OF SMA NEGERI 3 BANDA ACEH - Hendra Kasmi; Teuku Mahmud (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is entitled "Application of the Mind Mapping model in improving the ability to write expository texts in class X MIPA 4 students at SMA Negeri 3 Banda Aceh". The problem to be studied in this research is how to apply the Mind Mapping model in improving the ability to write expository texts in class X MIPA 4 students at SMA Negeri 3 Banda Aceh. This research aims to determine the application of the Mind Mapping model in improving the ability to write expository texts in class X MIPA 4 students at SMA Negeri 3 Banda Aceh. The type of research used in this research is Classroom Action Research (PTK). Meanwhile, the approach used in this research is a qualitative approach. The results of this research show that the increase in students' ability to write expository texts in cycle I is still low. So the researcher drew conclusions to carry out cycle II. After taking action to improve the ability to write expository texts using the Mind Mapping model, and the results in cycle II, student scores increased and the percentage of success for children was Incomplete (TT).